ST-35X Dynamic responses of reinforced concrete frames under single column removal scenario - Steven Lucianto (2016)
The ability of a building to mitigate progressive collapse is the main interest with increasing number of terrorist attacks. Using column removal scenario, Alternate Load Path (ALP) approach is one of the direct methods to mitigate progressive collapse.